Penyuluhan Pengelolahan Ekonomi Rumah Tangga Ibu PKK Kecamatan Maitara Selatan - Musdar Muhammad; Salha Marasaoly; Muhammad Zais M. Samiun (FKIP, Universitas Palangka Raya, 2023)
Maitara Island is a tourist destination, there are local tourist visits, visits for tourism, in addition to tourists enjoying the natural beauty of Maitra Island then, it cannot be separated from consumption, therefore, the provision of healthy food and drinks that must be provided by the community, especially mothers on Maitra Island, the development of tourism today, presents typical culinary problems in the area. The PKM methodtargets activities to mothers on the island of Maitara. This method of implementing community service uses the method; Lectures, Practices and Mentoring Participants. The results of the PKM on Sunday, October 5, 2023, took place at the village office, and 30 people were present for this PKM activity, who were mothers in Maitara Salatan village. In general, still managing the results of the husband's income to consume daily needs, and children's education, not used to do seving (savings), other problems there is no training on improving skills to produce products to sell, adding to produce.